Doing nothing: Anthropology sits at the same table with contemporary art in Lisbon and Tbilisi. (December 2018) - Martínez, Francisco
This article proposes an artistic performance to reflect on the labour of fieldwork. The experimental method consists in installing myself at a café in Lisbon and Tbilisi for 35 hours beyond the reach of smartphones and laptops and then doing nothing. Across this exercise, time slows, opening a clearer window into ordinary life. The intervention raises questions about the way digital technologies transform the temporality and experience of ethnographic fieldwork. The essay sets up to make a methodological contribution to a growing literature on 'inactivity' and about experimental methods, reminding us that observation is a tiring physical experience and that slow time is correlated with anthropological quality. Doing nothing appears as a slow time being in front of others, which enables a break of consciousness, suspends politics of relevance, and leaves space for serendipity and embodied imagination.